2014
DOI: 10.1080/14682753.2014.960766
|View full text |Cite
|
Sign up to set email alerts
|

Feast and famine? Local television news workers expand the offerings but say they are hungry for quality journalism

Abstract: By the nature of the work, TV newsworkers face a time famine: Too much to do in too little time. The famine has been compounded in recent years as local newsrooms produce content for two-and three-screen audiences. Chaos Theory says that even during chaotic times there are constants, such as deadlines and breaking news obligations. This study of 877 broadcast journalists examines their perceptions of work quality in light of organizational support, job satisfaction, work overload and autonomy. Results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 14 publications
(18 reference statements)
3
19
0
Order By: Relevance
“…Research on the work of television journalists and its changes stresses the influence of commercialization and technological developments and concludes that the working conditions of television journalists are worsening due to longer working hours, multiskilling, deprofessionalization and increasing precarity (increase in freelance workers, see Ursell, 2000). Two studies on job satisfaction among U.S. television news workers (Reinardy and Bacon, 2014;Reinardy, 2014) conclude that poor leadership, low pay, no future career prospects and being overworked are the most serious issues. Previous research has shown that job (dis)satisfaction is linked to salary, job security, work autonomy, quality of journalism, leadership competence, commercialization of news production and support from the media organization (for an overview see Reinardy and Bacon, 2014;Reinardy, 2014).…”
Section: Camera Reporters As News Workersmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on the work of television journalists and its changes stresses the influence of commercialization and technological developments and concludes that the working conditions of television journalists are worsening due to longer working hours, multiskilling, deprofessionalization and increasing precarity (increase in freelance workers, see Ursell, 2000). Two studies on job satisfaction among U.S. television news workers (Reinardy and Bacon, 2014;Reinardy, 2014) conclude that poor leadership, low pay, no future career prospects and being overworked are the most serious issues. Previous research has shown that job (dis)satisfaction is linked to salary, job security, work autonomy, quality of journalism, leadership competence, commercialization of news production and support from the media organization (for an overview see Reinardy and Bacon, 2014;Reinardy, 2014).…”
Section: Camera Reporters As News Workersmentioning
confidence: 99%
“…Two studies on job satisfaction among US television news workers (Reinardy, 2014; Reinardy and Bacon, 2014) conclude that poor leadership, low pay, no future career prospects and being overworked are the most serious issues. Previous research has shown that job (dis)satisfaction is linked to salary, job security, work autonomy, quality of journalism, leadership competence, commercialization of news production and support from the media organization (Reinardy, 2014; Reinardy and Bacon, 2014). In comparison, ‘broadcast journalists were most satisfied in their jobs when they thought managers demonstrated concern for the needs of subordinates’ (Reinardy, 2014: 858).…”
Section: Camera Reporters As News Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the U.S., Reinardy has previously focused, through interviews and surveys, on journalists who have remained in newsrooms depleted by layoffs and rapid changes in work practices over the course of the last decade (Reinardy 2011;Reinardy and Greenwood 2011;Reinardy and Bacon 2014). Significantly, his recent characterization of contemporary news workers as a "lost generation" (Reinardy 2017) included journalists who have remained in their roles as well as those who have departed (Lee 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This resource-intensive activity faces challenges in many local television newsrooms, where managers are demanding more output from reporters (Higgins-Dobney and Sussman 2013; Papper 2015b) while providing less financial support (Holcomb, Mitchell, and Purcell 2015;Jones 2013). As a result, in-depth reporting has decreased, while the focus on more cost-effective superficial stories has increased (see, e.g., Higgins-Dobney and Sussman 2013; Jurkowitz et al 2013;Reinardy and Bacon 2014). Higgins-Dobney and Sussman (2013, 857) found that many investigative television reporters now double as general assignment reporters and are expected to produce Digital Journalism, 2016 http://dx.doi.org/10.1080/21670811.2016.1175312 Ó 2016 Informa UK Limited, trading as Taylor & Francis Group stories daily: "There is little or no time permitted to investigate stories in-depth or add creativity to storytelling … often, what passes for investigative reporting involves nothing more than making a few phone calls."…”
Section: Introductionmentioning
confidence: 97%